EFFECT OF INTEGRATED NUTRIENT MANAGEMENT AND SPACING ON GROWTH AND YIELD PARAMETERS OF BLACK GRAM CV. LBG-625 (RASHMI) - N. AMRUTA,; J. B. MARUTHI,; G. SARIKA,; C. DEEPIKA, (The Bioscan, 2015)
A field experiment was conducted at Department of Seed Science and Technology, GKVK, UAS, Bangalore during kharif 2012 to assess the response of nutrient levels and spacing on growth and yield attributes of Black gram cv. LBG-625 (Rashmi). Experimental results revealed that fertilizer application of 50:100:100 NPK kg ha-1+ Black gram rhizobia (250 g ha-1) + PSB- Bacillus megaterium (250 g ha-1) with the spacing of 60 x 10 cm recorded significantly higher number of branches plant-1 (5.60), number of leaves plant-1 (29.87), plant spread plant-1 (756.00), number of cluster plant-1 (14.07), number of pods cluster-1 (22.60), number of pods plant-1 (54.40), pod weight plant-1 (g) (22.60), seed recovery per cent (98.45) and processed seed yield (q ha-1) (15.83) as compared to rest of the treatments. Hence, it can be concluded that the application of 50:100:100 NPK kg ha-1+ Black gram rhizobia (250 g ha-1) + PSB- Bacillus megaterium (250 g ha-1) with the spacing of 60 x 10 cm would be useful to enhance the productivity of black gram. The conjunctive use of inorganic fertilizers and biofertilizer may be suggested for higher productivity along with overall betterment.